Designing markets, governing data: Engineering value in the American healthcare system - Linda Huber (Big Data & Society, 2025)
In crucial sectors like healthcare, education, and housing, policymakers are turning to the tools of market design to incentivize public and private actors to more efficiently and effectively produce the public good. Although market design has been a key policymaking tool for decades, datafication is increasingly central to this technocratic tinkering. This article explores a project of datafied market redesign in the U.S. healthcare industry, demonstrating that emerging federal health data regulations are designed to enable the state to more precisely quantify, and thereby incentivize, the production of “valuable” care. This case study demonstrates how both the public good and crucial data infrastructures are constrained through their enactment within market-based modes of governance. As this data-solutionism for extractive markets becomes a more prevalent mode of governance—particularly in areas like climate change—we must find alternative mechanisms for collectively defining the public good, and for achieving corporate accountability beyond financial incentive structures.